Fungsi Humas Bank Jatim sebagai Fasilitator Sosialisasi dan Komunikasi Internal Mobile Banking JConnect - Setyo Sari, Annisa (Journal of Islamic Economics Studies and Practices, 2023)
The aim of innovation is to improve the performance of sharia banking. Innovation aims to improve product quality and service, design better products, extend product life cycles, meet customer needs and demands, develop new products and services, new organizational models, and new marketing strategies in addition to saving costs. To generate interest in the products and services offered by Bank Jatim Syariah KC Kediri branch, innovative products and services must be developed. Mobile banking is an example of Bank Jatims approach and dedication in offering digital services to the general public to facilitate transactions. The rise of the digital era is the cause of the high volume of digital transactions in Indonesia. This causes banks to compete with each other to provide the best service to the public. In this case, public relations can help management as a communication facilitator. Mediator and communicator to ensure that the public hears what management has to say and what management says an organization needs to function well. Bank Jatims public relations goal is to build strong relationships with communities, individuals and groups while increasing brand awareness. Observing the importance of the role of public relations as a communication channel makes it very interesting to research. This research methodology uses a case study format and qualitative methodology. Investigation of research findings shows that the role of Bank Jatim PR communication facilitator uses a PR approach in four steps in JConnect socialization, which includes defining the problem, organizing and setting, action, and assessing the initiative.